Heat transfer enhancement in a channel with rib-groove turbulators - Kaewkohkiat, Y.; Kongkaitpaiboon, V.; Eiamsa-Ard, S.; Pimsarn, M. (My University, 2010)
This paper presents the effects of the rib-groove turbulators on the heat transfer and friction characteristics in a rectangular channel. The experiments encompass the Reynolds number range from 1800 to 10,000; pitch ratios (PR=P/e) 6.6-13.3 by using air as the working fluid. The obtained results demonstrate that heat transfer rate in term of Nusselt number (Nu) increases with the increase of Reynolds number, whereas friction factor (f) shows the opposite trend. Both Nusselt number and friction factor increase with decreasing pitch ratio. It is also observed that heat transfer rate and friction factor for the channels with rib-groove turbulators are higher than those for the smooth channel under similar test conditions. In addition, the correlations for heat transfer rate in term of Nusselt number (Nu) and friction factor (f) for channel with rib-groove turbulators are also presented. © 2010 American Institute of Physics.
Keywords: Channel; Friction factor; Groove; Heat transfer; Rib; Turbulence flow